Diurnal Variation and Health Risk Assessment of Anthropogenic VOCs Concentrations in Abidjan, Côte d'Ivoire: a Comparative Study of Traffic and Domestic Fire Sites - Julien Bahino; Pamela Dominutti; Sékou Keita; Madina Doumbia; Marcellin Adon; Aurélie Colomb; Cathy Liousse; N’Datchoh Evelyne Touré; Agnès Borbon; Véronique Yoboue (Aerosol and Air Quality Research)
Abstract This study, part of the DACCIWA-FP7-WP2 project, aims to characterise urban air pollution in Abidjan (Côte d’Ivoire) and health risk associated with volatile organic compounds (VOCs). Two contrasting urban sites were examined. A traffic site in Adjamé and a domestic fire site in Yopougon. Air samples were collected using both manual and electric pumps and analysed by gas chromatography, which identified sixteen VOCs, including aromatics, monoterpenes, alkanes and alkenes (C5-C10). The daily average concentrations of total VOCs were similar between the two sites with 85.45 µg m−3 and 84.6 µg m−3 at the traffic and domestic fire sites, respectively. However, significant diurnal differences were observed. The traffic site had two peaks during the morning and evening rush hours, while the domestic fire site had a single peak in the morning, associated with cooking and smoking food. BTEX compounds (benzene, toluene, ethylbenzene, xylenes), were predominant, accounting for 86% of the total VOCs observed at the domestic fire site and 79.6% at the traffic site. BTEX concentrations in Abidjan are among the highest recorded in urban areas across Africa and worldwide, although still lower than in cities such as Accra, Lagos and Athens. In particular, benzene levels in Yopougon site (9.8 µg m−3) exceed the European safety limit of 5 µg m−3 and are almost double those in Adjamé (4.51 µg m−3). The Lifetime Cancer Risk (LCR) for benzene is 6.72 × 10–2 at the domestic fire site and 3.1 × 10–2 at the traffic site, well above the recommended safety threshold of 1.0 × 10–6. These levels indicate a serious health risk for sensitive populations exposed to chronic benzene inhalation. While non-carcinogenic risks remain relatively low, the cancer risks, particularly linked to benzene and ethylbenzene, exceed acceptable limits. These findings underscore the urgent need for regulatory action and targeted air quality management strategies in Abidjan to reduce exposure to harmful pollutants. Graphical Abstract